2017
DOI: 10.1128/aac.02761-16
|View full text |Cite
|
Sign up to set email alerts
|

The Nonantibiotic Macrolide EM703 Improves Survival in a Model of Quinolone-Treated Pseudomonas aeruginosa Airway Infection

Abstract: Macrolide antibiotics are used as anti-inflammatory agents, e.g., for prevention of exacerbations in chronic obstructive pulmonary disease and cystic fibrosis. Several studies have shown improved outcomes after the addition of macrolides to ␤-lactam antibiotics for treatment of severe community-acquired pneumonia. However, a beneficial effect of macrolides in treating Gram-negative bacterial airway infections, e.g., those caused by Pseudomonas aeruginosa, remains to be shown. Macrolide antibiotics have signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
2
9
1
Order By: Relevance
“…We found only one study that specifically assessed the effects of a modified macrolide, EM703, lacking antibiotic activity, as an adjunct anti-inflammatory treatment in association with levofloxacin, in a PA acute pneumonia murine model ( Kasetty et al, 2017 ). Interestingly, all mice receiving levofloxacin 4 h after infection died within 72 h, whereas no bacteria were detected in their lungs 48 h after infection.…”
Section: Efficacy Of Macrolides Combined Therapy In Animal Models Of mentioning
confidence: 99%
“…We found only one study that specifically assessed the effects of a modified macrolide, EM703, lacking antibiotic activity, as an adjunct anti-inflammatory treatment in association with levofloxacin, in a PA acute pneumonia murine model ( Kasetty et al, 2017 ). Interestingly, all mice receiving levofloxacin 4 h after infection died within 72 h, whereas no bacteria were detected in their lungs 48 h after infection.…”
Section: Efficacy Of Macrolides Combined Therapy In Animal Models Of mentioning
confidence: 99%
“…9) This bifunctional mode of macrolides is thought to be ideal for the treatment of respiratory diseases, but the risk for bacterial resistance is still considered as an important issue in the clinic. 10,27) In this connection, recent studies focused on the pharmacological action of non-antibiotic macrolide derivatives. 20,[28][29][30] In the present study, we showed that macrolides directly attenuate constitutive airway ENaC function in vitro and demonstrated the modulatory roles of azithromycin in C57BL/6J-βENaC-Tg mice, possibly through the inhibition of constitutive ENaC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria and peptide/levofloxacin were administered through the i.p. route at different sides of stomach . Each group contained five mice.…”
Section: Methodsmentioning
confidence: 99%